Technical-tactical preparation of Austrian judoka at the Austrian national championships and the number of associated injuries - Handler, M.; Moser, M.; Toca-Herrera, J.; Burtscher, M. (SportRxiv, 2017)
Background & study aim: The first Austrian Judo championships took place in 1947. Since then there hasn`t been any scientific literature about technical, tactical or physical preparation about the participants. In addition, there hasn`t been any trauma statistics of Austrian tournaments either. Some scientific studies describe Judo associated injuries on Olympic or international level, but how gentle is the "gentle way"? Are there any associations between techniques and injuries?